Analysis of the need for ICT (Information and Communication Technology) based biology teaching materials at the high school level - Musdahlipah Musdahlipah; Ervan Johan Wicaksana; Upik Yelianti; Puji Rizky Widyaningsih (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Based on the demands of the learning curriculum in the classroom, it must create an atmosphere that is active, creative, analytical, and critical in solving problems through the development of thinking skills. However, the involvement of students in learning activities in class is still low. The research aims to determine the need for ICT-based biology teaching materials and the constraints in applying them. The research used a qualitative descriptive approach, the subjects of the research were class X students, biology teachers, ICT teachers, and Deputy Principal for Curriculum. The sampling technique used purposive sampling technique. The research procedure goes through three stages, namely preparation, implementation, and member check. Based on the research results, the biology learning process still uses contextual models and lecture methods. It is also that 83.3% of students said they needed ICT teaching materials to understand the material, concretize abstract material, and increase interaction in the learning process. Constraints in implementing ICT-based teaching materials are classified into physical and non-physical facilities. Physical facilities in the form of learning equipment, while non-physical means lack time and lack of training in designing ICT-integrated learning. Teacher expertise in ICT-based learning needs to be trained so that students can be more active in the learning process.AbstrakBerdasarkan tuntutan kurikulum pembelajaran di kelas harus menciptakan suasana yang aktif, kreatif, analisis, dan kritis dalam pemecahan masalah melalui pengembangan keterampilan berpikir. Namun keterlibatan peserta didik dalam kegiatan pembelajaran di kelas masih rendah. Penelitian bertujuan mengetahui kebutuhan bahan ajar biologi berbasis TIK dan kendala dalam menerapkannya. Penelitian menggunakan pendekatan deskriptif kualitatif, subjek penelitian adalah peserta didik kelas X, guru biologi, guru TIK dan Wakil Kepala Sekolah Bidang Kurikulum. Teknik pengambilan sampel menggunakan teknik purposive sampling. Prosedur penelitian melalui tiga tahap yaitu persiapan, pelaksanaan, dan member check. Berdasarkan hasil penelitian, proses pembelajaran biologi masih menggunakan model kontekstual dan metode ceramah. Diketahui pula 83,3% peserta didik mengungkapkan membutuhkan bahan ajar TIK untuk memahami materi, mengkonkretkan materi yang abstrak, serta meningkatkan interaksi dalam proses pembelajaran. Kendala dalam menerapkan bahan ajar berbasis TIK digolongkan menjadi dua yaitu sarana fisik dan non fisik. Sarana fisik berupa peralatan belajar, sedangkan secara non fisik adalah kekurangan waktu dan belum terlatihnya dalam mendesain pembelajaran terintegrasi TIK. Keahliah guru dalam melaksanakan pembelajaran berbasis TIK perlu dilatih agar peserta didik dapat lebih aktif dalam proses pembelajaran.